Messengers from the Stars. Episode IV Lisbon, Portugal, 16 - 18 November 2016 - Kujundzic N (CROATIAN ASSOC RESEARCHERS CHILDRENS LITERATURE, 2022)
Report on the 4th Messengers from the Stars international conference